Carotenoids from ulam: bridging traditional knowledge with modern halal pharmaceutical needs - Mohd Hatta, Farah Ayuni; Mat Ali, Qurratu Aini; Othman, Rashidi; Amin, Latifah (Nova Science Publishers, Inc., 2026)
The halal pharmaceutical industry has gained interest beyond the Muslim consumer market due to the trust and high-quality assurance offered by halal certification. Synthetic active pharmaceutical ingredients (APIs) can have long-term negative effects on human health and contribute to environmental degradation. In this context, there is a growing interest in natural and halal APIs that can offer positive health effects. Fruits and vegetables are excellent sources of provitamin A, with carotenoids providing between 70% to 90% of the daily requirement. Additionally, ulam, a traditional Malay vegetable, is a rich source of carotenoids with proven nutritional benefits besides having good antioxidant and antimicrobial properties. As a result, ulam has great potential to offer positive health effects as a dietary source and as a natural and halal APIs. By incorporating ulam-based natural APIs, the pharmaceutical industry can contribute to healthier and sustainable outcomes for both individuals and the environment.